New aids to the prenatal diagnosis of achondroplasia. (16th November 2010) - Khalil, A; Meaney, C; Chitty, L
Abstract : Background: Suspicion of skeletal dysplasias subsequent to the detection of significant shortening of fetal long bones can pose a diagnostic dilemma as accurate diagnosis before birth can be challenging in the absence of a family history. Targeted molecular diagnosis is the most reliable approach, but this requires invasive testing and a high level of suspicion of the underlying pathology following detailed ultrasound examination to allow for targeted molecular analysis. The advent of non-invasive prenatal diagnosis using cell free fetal DNA (cffDNA) combined with expert ultrasound offers the potential for a safe, reliable approach to diagnosis in some conditions. Here the authors describe the non-invasive approach to the diagnosis of achondroplasia. Methods: All cases of achondroplasia seen in our fetal medicine units were identified, ultrasound findings and measurements ascertained. Since 2007 the Regional Genetics Laboratory at GOSH has offered cffDNA testing in selected cases. All those referred for diagnosis of achondroplasia were ascertained and cffDNA results compared with outcome at birth. Results: Fetal size charts were constructed serial measurements from 16 fetuses with Achondroplasia and frequency of sonographic features correlated with gestation. cffDNA analysis correctly confirmed the diagnosis of Achondroplasia in three fetuses and excluded it in a fourth. Fetal size charts and associated abnormities will be presented. Conclusion: Using a combination of ultrasound features and reference to size charts for fetuses with achondroplasia together with analysis of cffDNA can offer safe, accurate prenatal diagnosis in this condition.